Astragaloside IV sensitizes non–small cell lung cancer cells to gefitinib potentially via regulation of SIRT6. Issue 4 (April 2017) - Dai, Peng-Chen; Liu, De-Ling; Zhang, Lei; Ye, Jia; Wang, Qing; Zhang, Hong-Wen; Lin, Xiu-Hua; Lai, Guo-Xiang
Astragaloside IV, the active component of Astragalus membranaceus, exhibits diverse biological roles including the anti-tumor activity. In this study, we evaluated the chemosensitive role of astragaloside IV in non–small cell lung cancer cells. Cell Counting Kit-8 analysis was performed to determine cell viability. Real-time polymerase chain reaction and western blot were used to measure the messenger RNA and protein expression. Results showed that astragaloside IV treatment could suppress the proliferation of non–small cell lung cancer cells. In addition, combined treatment with astragaloside IV remarkably enhanced the chemosensitivity to gefitinib in three non–small cell lung cancer cell lines including NCI-H1299, HCC827, and A549. Furthermore, compared with gefitinib-treated cells, the messenger RNA expression of SIRT6 was obviously increased in non–small cell lung cancer cells treated with gefitinib combined with astragaloside IV. In addition, downregulation of SIRT6 was accomplished using small interference RNA technology. As a result, SIRT6 inhibition abolished the sensitization role of astragaloside IV in non–small cell lung cancer cells. Taken together, these data demonstrated that astragaloside IV sensitized tumor cells to gefitinib via regulation of SIRT6, suggesting that astragaloside IV may serve as potential therapeutic approach for lung cancer.